A non-contacting system for rail neutral temperature and stress measurements: Concept development. (January 2021) - Knopf, Katelyn; Rizos, Dimitris C; Qian, Yu; Sutton, Michael
Continuous welded rail has become the standard in modern railway track construction around the world because it alleviates well-documented disadvantages of rail joints in a track. Continuous welded rail practice results in long segments of continuous rail in track that will develop significant thermal longitudinal stresses due to the absence of expansion joints. Before a continuous welded rail is laid, the rail is free of thermal stresses; the temperature at that time is known as the rail neutral temperature. The design rail neutral temperature is calculated based on local climate projections. As a continuous welded rail is laid, it may be stretched or compressed if the current temperature is not within the calculated design rail neutral temperature range, prior to anchoring the rail down. Upon anchoring, as temperatures deviate from the rail neutral temperature, significant tensile or compressive longitudinal stresses develop, leading to a track buckling or rail pull-apart that compromise the integrity of the track and the safety of train operation. Existing methods to estimate the rail neutral temperature and determine the state of stress in the rail have significant shortcomings related to the ease of implementation, system complexity, practicality, reliability, simplicity, cost, and instrumentation demands. We propose a novel concept for measuring stress in rail segments and determining the rail neutral temperature. The proposed method is based on measurements of nonuniform deformations of the rail under thermal loading, as observed in computer simulations and laboratory investigations. The implementation uses thermal imaging and three-dimensional stereo-digital image correlation technology to acquire full-field deformations. The acquired data are processed to estimate rail neutral temperature and quantify the longitudinal stress in the rail. This article presents the analytical and experimental work that led to the conception of the method and introduces the systematic approach to develop the method along with verification and validation studies.